A study on awareness and disposal practices of unused and expired medicines by consumers - D., Bhavika; Vaseem, Ayesha; Singh C., Sunil Pal (International Journal of Basic & Clinical Pharmacology, 2020)
Background: Hazards to the environment due to improper drug disposal practices is an issue of concern. The prescription drugs, disposed into trash /sewage, consequently enter into surface waters and contaminate even drinking water. In view of the potential hazards posed due to improper storage and disposal of medicines, evaluation of the awareness of the consumers and educating them about proper disposal methods is required. The aim of present study was to evaluate the awareness and practice of drug disposal among the population. Methods: A cross sectional, observational study was conducted at Rural Health Centre (RHTC) of Kamineni Academy of Medical Sciences and Research Centre with the patients visiting the RHTC as the study subjects. A predesigned questionnaire was used to evaluate the awareness and disposal practices of unused and expired medicines by the respondents. Results: On analysis it was observed that 80 (57%) of the respondents procure medicines from health care centre. A total of 97 (69%) respondents possess unused/leftover medicines at home, 54 (39%) of the respondents mentioned the reason to be due to self discontinuation. Among the class of drugs left unused antibiotics constituted 13%, antipyretics 6%, analgesics 6%. 49% of the respondents dispose unused medicines in domestic trash, 24% flush down toilet/sink. A majority of 121 (86%) opined that awareness must be made created. Conclusions: In present study it was observed that many of the respondents possessed leftover medicines and were unaware of the hazards of improper disposal of medicines. Thus, there is a need for proper educational and regulatory interventions.